The vital illusion - Baudrillard, Jean (Wellek Library lecture series at the University of California, Irvine., 2000)
Aren't we actually sick of sex, of difference, of emancipation, of culture? With this provocative taunt, the indomitable sociologist Jean Baudrillard challenges us to face up to our deadly, technologically empowered renunciation of mortality and subjec.